Sn(SO4)2·2H2O from synchrotron powder data - Øystein Slagtern Fjellvåg; Helmer Fjellvåg (IUCrData)
Tin(IV) sulfate dihydrate, Sn(SO4)2·2H2O, was prepared in a reflux of sulfuric acid under oxidizing conditions. Its crystal structure was determined from powder synchrotron X-ray diffraction data and is constructed of (100) layers of [SnO4(H2O)2] octahedra (point group symmetry 1) corner-connected by sulfate tetrahedra. Hydrogen bonds of moderate strength between the water molecules and sulfate O atoms hold the layers together.